2013
DOI: 10.1007/s00405-013-2431-2
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve canal dehiscence in chronic otitis media without cholesteatoma

Abstract: The information on incidence of the facial nerve canal dehiscence in chronic otitis media is important for surgeons. The purpose of this study is to disclose the histopathologic findings of facial nerve canal dehiscence in human temporal bones with chronic otitis media. We divided the human temporal bones into two groups (age 4 years, and under 4 years of age). We evaluated the incidence and the area of the facial nerve canal dehiscence in chronic otitis media under light microscopy. Age-matched normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In early childhood, middle ear inflammations may barely influence the development of the facial canal. 7 Almost surgical reports regarding facial canal destruction have been conducted commonly with patients who have undergone chronic otitis surgery with or without cholesteatoma. 8 The incidence of facial canal destruction ranges from 0.5% to 74%, and is mostly higher in histologic studies than in surgical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early childhood, middle ear inflammations may barely influence the development of the facial canal. 7 Almost surgical reports regarding facial canal destruction have been conducted commonly with patients who have undergone chronic otitis surgery with or without cholesteatoma. 8 The incidence of facial canal destruction ranges from 0.5% to 74%, and is mostly higher in histologic studies than in surgical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In early childhood, middle ear inflammations may barely influence the development of the facial canal. 7 …”
Section: Discussionmentioning
confidence: 99%
“…4 There are several studies on facial nerve canal dehiscence (FCD) and COM in the literature. [4][5][6] However, a heterogeneity is found in these literature in terms of cholesteatoma spread and cholesteatoma presence. Also, limited data are found in the literature about the relationship between FCD and other damaged anatomical structures in cases with cholesteatoma.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of dehiscence was more common in women but the results were not statistically significant. Nomiya et al [15] reported the high incidence of facial nerve canal dehiscence in chronic otitis media. The incidence was 88.2% in the group of subjects aged under four years, and was 68.9% in the group of subjects aged four years and older.…”
Section: Discussionmentioning
confidence: 99%